The Relationship Between Self-Esteem and Self-Identity in Early Adulthood with the Bandwagon Effect in the Use of Luxury Fashion - Arisanti Salsabila Putri; Erik Saut H.Hutahaean; Ferdy Muzzamil (Socrates: Journal of Education, Philosophy and Psychology, 2026)
This study aimed to determine the relationship between self-esteem and self-identity in early adulthood within the context of the bandwagon effect in the use of luxury fashion. The phenomenon of luxury fashion consumption among early adults has increased alongside the influence of social media, social trends, and the need for social recognition. This research employed a quantitative approach with a correlational method. The participants consisted of 120 early adults in Bekasi City who actively use social media and wear luxury fashion products, selected through purposive sampling. The research instruments used were the Ego Identity Process Questionnaire (EIPQ) to measure self-identity and the Rosenberg Self-Esteem Scale (RSES) to measure self-esteem. Data analysis was conducted using Kendall’s Tau B correlation analysis because the data were not normally distributed. The results showed a significant positive relationship between self-esteem and self-identity, with a correlation coefficient value τb = 0,692 and a significance value of p < 0.001. This indicates that higher self-esteem is associated with higher self-identity. Conversely, lower self-esteem tends to be related to a less stable self-identity and greater susceptibility to social trends in the use of luxury fashion.